Tourism Events: Typologies and Management - bahram ranjbarian; mohamad zahedi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2004)
Tourism attractions of a destination are not limited to natural and historical sites, and art centers. Indeed every event could be an important source of attracting tourists, especially in cases that. destinations have less well known physical attraction. Tourism events have vast variety with respect to their types: from rehearsal of songs by residents in the city of Can in France, to Oscar Film Festival, from horse racing in Turkoman Sahara, to Athena Olympic games. and from a religious ceremony in Saint Tattoos church in Azerbaijan. to hajj pilgrim, all of them provide religious. business, recreation. and shopping motives for people from all over the world to travel. Now a day it seems that schedules for holding such events have increasing trend . and destinations from all over the world are competing to prepare new and attractive tourism events. Since tourism development is a national policy in Iran economy. therefore designing and planning for new tourism events could provide a great opportunity to us. But it is obvious that the first step in this development is to acquire the require knowledge about the types and their management. In this article the types and key points in tourism event planning and management have been demonstrated.